Distinct Hepatic Gene‐Expression Patterns of NAFLD in Patients With Obesity. Issue 1 (11th August 2021) - Subudhi, Sonu; Drescher, Hannah K.; Dichtel, Laura E.; Bartsch, Lea M.; Chung, Raymond T.; Hutter, Matthew M.; Gee, Denise W.; Meireles, Ozanan R.; Witkowski, Elan R.; Gelrud, Louis; Masia, Ricard; Osganian, Stephanie A.; et al.
Abstract : Approaches to manage nonalcoholic fatty liver disease (NAFLD) are limited by an incomplete understanding of disease pathogenesis. The aim of this study was to identify hepatic gene‐expression patterns associated with different patterns of liver injury in a high‐risk cohort of adults with obesity. Using the NanoString Technologies (Seattle, WA) nCounter assay, we quantified expression of 795 genes, hypothesized to be involved in hepatic fibrosis, inflammation, and steatosis, in liver tissue from 318 adults with obesity. Liver specimens were categorized into four distinct NAFLD phenotypes: normal liver histology (NLH), steatosis only (steatosis), nonalcoholic steatohepatitis without fibrosis (NASH F0), and NASH with fibrosis stage 1‐4 (NASH F1‐F4). One hundred twenty‐five genes were significantly increasing or decreasing as NAFLD pathology progressed. Compared with NLH, NASH F0 was characterized by increased inflammatory gene expression, such as gamma‐interferon‐inducible lysosomal thiol reductase (IFI30) and chemokine (C‐X‐C motif) ligand 9 (CXCL9), while complement and coagulation related genes, such as C9 and complement component 4 binding protein beta (C4BPB), were reduced. In the presence of NASH F1‐F4, extracellular matrix degrading proteinases and profibrotic/scar deposition genes, such as collagens and transforming growth factor beta 1 (TGFB1), were simultaneously increased, suggesting a dynamic state of tissue remodeling. Conclusion: In adults with obesity, distinct states of NAFLD are associated with intrahepatic perturbations in genes related to inflammation, complement and coagulation pathways, and tissue remodeling. These data provide insights into the dynamic pathogenesis of NAFLD in high‐risk individuals.